Paravertebral Block in the Treatment of Patients With Blunt Chest Trauma - V. G. Kotandzhian; E. A. Tarabrin; Sh. N. Danielian; I. U. Ibavov; T. E. Kallagov; S. A. Korneeva; I. E. Popova (Неотложная медицинская помощь)
The study was conducted in the Thoracoabdominal Department of the N.V. Sklifosovsky Research Institute for Emergency Medicine to explore the role of paravertebral block in the treatment of blunt chest trauma. The study included 715 patients with isolated chest trauma hospitalized between January 1, 2020 and August 2021. 55 patients received analgesic therapy in the form of paravertebral block. The comparison group included 660 patients who did not undergo paravertebral block, in their case pain relief was provided by systemic administration of analgesics. The compared groups did not differ significantly in sex and age composition. There were also no differences in the frequency of chronic diseases and interpleural complications. There were no significant complications during the block. The comparison revealed a significant decrease in the incidence of pleurisy and a shorter length of stay in hospital. Paravertebral block is an effective and safe method of pain management for patients with blunt chest trauma. The use of this technique reduces the incidence of post-traumatic pleurisy and duration of hospitalization.